Identifying the Optimal Number of Neoadjuvant Chemotherapy Cycles in Patients with Muscle Invasive Bladder Cancer. Issue 1 (27th January 2022) - D'Andrea, David; Black, Peter C.; Zargar, Homayoun; Dinney, Colin P.; Soria, Francesco; Cookson, Michael S.; Montgomery, Jeffrey S.; Kassouf, Wassim; Dall'Era, Marc A.; Sridhar, Srikala S.; McGrath, John S.; Wright, Jonathan L.; et al.
Abstract : Purpose: We investigated the pathological response rates and survival associated with 3 vs 4 cycles of cisplatin-based neoadjuvant chemotherapy (NAC) in patients with cT2-4N0M0 muscle invasive bladder cancer. Materials and Methods: In this cohort study we analyzed clinical data of 828 patients treated with NAC and radical cystectomy between 2000 and 2020. A total of 384 and 444 patients were treated with 3 and 4 cycles of NAC, respectively. Pathological objective response (pOR; ypT0-Ta-Tis-T1 N0), pathological complete response (pCR; ypT0 N0), cancer-specific survival and overall survival were investigated. Results: pOR and pCR were achieved in 378 (45%; 95% CI 42, 49) and 207 (25%; 95% CI 22, 28) patients, respectively. Patients treated with 4 cycles of NAC had higher pOR (49% vs 42%, p=0.03) and pCR (28% vs 21%, p=0.02) rates compared to those treated with 3 cycles. This effect was confirmed on multivariable logistic regression analysis (pOR OR 1.46 p=0.008, pCR OR 1.57, p=0.007). On multivariable Cox regression analysis, 4 cycles of NAC were significantly associated with overall survival (HR 0.68; 95% CI 0.49, 0.94; p=0.02) but not with cancer-specific survival (HR 0.72; 95% CI 0.50, 1.04; p=0.08). Conclusions: Four cycles of NAC achieved better pathological response and survival compared to 3 cycles. These findings may aid clinicians in counseling patients and serve as a benchmark for prospective trials. Prospective validation of these findings and assessment of cumulative toxicity derived from an increased number of cycles are needed.